The in vivo crude protein digestibility of soybean species cultivated in Hungary - Sudár, Gergő; Horváth, Alexandra Rebeka; Jakab, Judit; Pósa, Roland; Halas, Veronika; Tossenberger, János (Acta Agraria Kaposváriensis, 2021)
The purpose of the trial was to use the mobile nylon bag technique to determine the crude protein digestibility and calculate the digestible protein yield of soybean varieties cultivated in Hungary. The trial was carried out with 10, double cannulated (duodenal- and PVTC-cannula) hybrid barrows with initial live weights of 40±3.5 kg. The experimental basal diets were formulated on a corn-wheat-barley-soybean basis according to the requierement of growing pigs (Tybirk, 2015). A total of 20 soybean varieties were tested in this experiment. After simulating gastric digestion the nylon bags were inserted into the duodenum of ten barrows through simple duodenal T-cannulae. Ten bags were administered to each pig daily. A total of 200 (10 samples/soybean variety) bags were inserted over a 4-day period. The mean, standard deviation, minimum and maximum values of the crude protein digestibility of soybean samples were calculated. The protein yields per hectare according to the crop yield and the protein content values and also the digestible protein yield values were calculated. To examine the relationship between crop yield and crude protein yield and also between crop yield and digestible crude protein yield regression analysis were used. The overall results of this experiment indicate that the average crude protein digestibility of the tested soybean varieties was 76.0%, with an absolute difference of 17.3% between the best and the least digestible varieties. ES Mentor variety reached the best digestible crude protein yield, with 1305.4 kg/ha. The variety with the lowest digestible crude protein yield was Boglár, with 752.3 kg/ha. The difference in digestible crude protein yield between these two varieties was 173.5%. In the correlation analysis between digestible crude protein content and yield for soybean varieties our results show that there is no correlation between the two factors. However, Aires, Prestopro, and ES Mentor should be highlighted among the varieties with above trend line results, as they have the best yield (4020 kg/ha; 4100 kg/ha, 4510 kg/ha) and digestible crude protein content (31%, 30.3%, and 28.9%). ES Mentor produced the fourth best digestible crude protein content (28.9%) with the best yield (4510 kg/ha).
Keywords: szójabab; emészthetőség; nejlonzacskó; hozam